2006
DOI: 10.1016/j.cell.2006.08.036
|View full text |Cite
|
Sign up to set email alerts
|

P68 RNA Helicase Mediates PDGF-Induced Epithelial Mesenchymal Transition by Displacing Axin from β-Catenin

Abstract: The nuclear p68 RNA helicase (referred to as p68) is a prototypical member of the DEAD box family of RNA helicases. The protein plays a very important role in early organ development. In the present study, we characterized the tyrosine phosphorylation of p68 under platelet-derived growth factor (PDGF) stimulation. We demonstrated that tyrosine phosphorylation of p68 at Y593 mediated PDGF-stimulated epithelial-mesenchymal transition (EMT). We showed that PDGF treatment led to phosphorylation of p68 at Y593 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
288
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(308 citation statements)
references
References 49 publications
16
288
4
Order By: Relevance
“…One intriguing possibility is that, depending on the cellular context, ddx5/ddx17-splicing activity or their transcriptional activity could dominate each other and this could participate in the dual function of ddx5 and ddx17 in cancer. In this context, several reports have indicated that the splicing and transcriptional activities of ddx5 and ddx17 can be modulated by different post-translational modifications that depend on cellular signaling pathways (Yang et al, 2006(Yang et al, , 2007Jacobs et al, 2007;Carter et al, 2010;Mooney et al, 2010a, b). In addition, several post-translational modifications of ddx5 or ddx17 have been shown to be altered in different cancers (Causevic et al, 2001;Yang et al, 2005).…”
Section: Ip Flagmentioning
confidence: 99%
See 1 more Smart Citation
“…One intriguing possibility is that, depending on the cellular context, ddx5/ddx17-splicing activity or their transcriptional activity could dominate each other and this could participate in the dual function of ddx5 and ddx17 in cancer. In this context, several reports have indicated that the splicing and transcriptional activities of ddx5 and ddx17 can be modulated by different post-translational modifications that depend on cellular signaling pathways (Yang et al, 2006(Yang et al, , 2007Jacobs et al, 2007;Carter et al, 2010;Mooney et al, 2010a, b). In addition, several post-translational modifications of ddx5 or ddx17 have been shown to be altered in different cancers (Causevic et al, 2001;Yang et al, 2005).…”
Section: Ip Flagmentioning
confidence: 99%
“…There are now many reports indicating that these multifunctional proteins have important implications for cancer development, as recently reviewed (Janknecht, 2010;FullerPace and Moore, 2011). For example, on one hand, as transcriptional coactivators of estrogen receptor alpha, they may contribute to the proliferative effect of estradiol on breast cancer cells (Wortham et al, 2009;Dutertre et al, 2010a) and, as coregulators of betacatenin, they may contribute to the epithelial to mesenchymal transition, which has been associated with breast cancer progression (Yang et al, 2006). On the other hand, as coactivators of p53 and Smad, ddx5/ ddx17 may exert tumor suppressor functions (Warner et al, 2004;Bates et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that β-catenin accumulation, a hallmark of Wnt activation, is particularly enhanced in the invasion front and metastasized colon cancer cells, suggesting that promotion of Wnt/β-catenin signaling is important for malignant progression 8 . Growth factors PDGF and HGF, as well as inflammatory cytokine TNF-α, have been shown to promote Wnt/β-catenin signaling activity in tumor cells [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Tyr phosphorylation of b-catenin leads to its stabilisation and nuclear signalling activity by decreasing its binding affinity to E-cadherin and the APC/GSKb/Axin destruction complex (Coluccia et al, 2007). Platelet-derived growth factor (PDGF) stimulation of HT-29 colorectal cancer cells increases b-catenin activation via p68-dependent inhibition of Ser/Thr phosphorylation by GSK3b (Yang et al, 2006).…”
Section: Stromal Cells Affecting Tumour Growth Nuclear B-catenin Accmentioning
confidence: 99%